2018
DOI: 10.37358/rc.18.4.6208
|View full text |Cite
|
Sign up to set email alerts
|

Castleman�s Disease - Clinical, Histological and Therapeutic Features

Abstract: Castleman�s disease (CD) is a rare and benign lymphoproliferative pathology, characterized by lymphoid tissue hyperplasia, process that can occur at any site of the lymphoid chain. The purpose of this paper is to review the existing data regarding Castleman�s disease etiopathogenesis and treatment. Considering the extent of the lymphoid tissue involvement Castleman�s disease can be classified as unicentric (UCD) and multicentric (MCD). Another classification of this pathology is based on the histopathological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 39 publications
(71 reference statements)
0
22
0
1
Order By: Relevance
“…It is accepted that a double J stent, after a procedure, eliminates the risk of hydronephrosis due to mucosal edema. On the other hand, the ureteral stent itself is associated with a certain degree of morbidity, including stent infiltration, ureteral mucosal erosion, flank pain and irritant discharge symptoms, especially in patients with previous comorbidities and reduced physiological resources [44][45][46][47]. Recent comparative studies have shown that procedural costs can be reduced by 30% if the postoperative stent is avoided [48].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is accepted that a double J stent, after a procedure, eliminates the risk of hydronephrosis due to mucosal edema. On the other hand, the ureteral stent itself is associated with a certain degree of morbidity, including stent infiltration, ureteral mucosal erosion, flank pain and irritant discharge symptoms, especially in patients with previous comorbidities and reduced physiological resources [44][45][46][47]. Recent comparative studies have shown that procedural costs can be reduced by 30% if the postoperative stent is avoided [48].…”
Section: Resultsmentioning
confidence: 99%
“…Computed tomography (CT) with no contrast is considered the gold standard investigation in reno-ureteral lithiasis pathology [6][7][8][9], providing information on localization, density and size of the stones [10][11][12][13].…”
Section: Abstract: Non-contrast Computer Tomography Stones Densitymentioning
confidence: 99%
“…The risk factors for developing kidney stones can be classified into three groups: endogenous causes (metabolic dysfunctions, endocrine diseases like hyperparathyroidism, tumors [13], gastric hypoacidity, etc. ), renal causes (kidney dysfunction, tubular disorders), and post-renal causes (malformations and urinary tract obstruction by extrinsec compresion or invasion [14][15][16][17], bladder pathology [18,19] or subvesical obstruction [20,21], post-surgical procedures [22,23], bacterial infections) [24].…”
mentioning
confidence: 99%
“…Current indications for stent placement include relief of ureteral obstruction, whether the cause is intrinsic (from a calculus, clot, or urothelial carcinoma, metastasis) or extrinsic (from external compression or mass effect) [5][6][7][8][9][10][11][12]. Most of these stents are placed for 2-3 weeks, but there are situations that require a longer period up to years.…”
mentioning
confidence: 99%